The Flypaper Effect in Germany: An East-West Comparison - Artem Korzhenevych; Sebastian Langer (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2016)
We investigate the effect of general-purpose transfers on different expenditure categories and tax rates in the municipalities of Saxony (eastern Germany) and North Rhine-Westphalia (western Germany). Findings from the panel data analysis suggest the existence of the "flypaper effect" - municipalities use transfers to increase expenditures but do not reduce taxes. For most expenditure subcategories the estimated coefficients are alike, suggesting similarity of spending priorities in the two federal states despite the differences in the transfer dependency. Targeted support of eastern municipalities could potentially explain few identified differences in the spending behavior.
urn:nbn:de:bsz:14-qucosa-213629
Keywords: H21; H70; H71; H72; H77; 330; Flypaper Effect; Local Government Expenditure; Transfers to Municipalities; Local Taxation